Detection of Anaplasma phagocytophilum in Ixodes angustus Ticks Found in the Magadan Region - A. V. Yamborko; Yu. V. Eremeeva (Проблемы особо опасных инфекций, 2014)
Reported is the event of detection of Anaplasma phagocytophilum in Ixodes angustus ticks using gene-diagnostic technique. Anaplasma DNA is identified in one of the nine samples of ixodic tick imago collected from common species of rodents in the suburbs of Magadan. The data obtained may be indicative of the existence of natural granulocytic anaplasmosis focus in the south of the Magadan Region where the agent persists in enzootic cycle: small mammals - Ixodes angustus.